086 Acceptance and Commitment Therapy to Increase Compliance to Intracavernosal Injection Use (ICI) Following Radical Prostatectomy (RP): Preliminary Results from a Randomized Control Trial. (1st May 2022) - Nelson, CJ; Tutino, R; Joshi, N; Schofield, E; Mulhall, JP
ABSTRACT: Introduction: ICI is the cornerstone of many erectile rehabilitation programs (ERP). However, compliance with ICI is historically low. This study tests a novel psychological intervention based on Acceptance and Commitment Therapy (ACT) concepts to help men reduce avoidance to ICI and commit to an ERP. Methods: This ongoing study recruits men starting in our ERP. The recruitment goal is N=220. Subjects are randomized to ERP+ACT or ERP+Enhanced Monitoring and Education (EME). ERP+ACT receive ERP plus 3 ACT Sessions (30-45min) and 10 ACT Booster Sessions (10min). ERP+EME receive ERP plus 3 EME Sessions (30-45min) and 10 EME Booster Sessions (10min) delivered by a nurse practitioner who monitors ICI use, answers questions, and provides education. The interventions are delivered over a year. Eligibility includes: within 9m post RP; functional pre-RP erections (≥6/10). Subjects are assessed at entry and every 6m for two years. The primary outcomes are number of penile injections/week (verified by syringe count), and compliance (defined as ≥2 injections/week). Secondary outcomes are: ED treatment satisfaction, sexual self-esteem and relationship quality, sexual bother, prostate cancer treatment regret, the psychological impact of cancer, and depressive symptoms. Preliminary 6m data is presented. Groups are compared with ANCOVA. Since these are preliminary analyses, if differences were not statistically significant, effect sizes (d) are reported (d=0.2, small effect; d=0.5, medium effect; d=0.8, large effect). Results: To date, 120 subjects have been randomized; 62 have completed the 6m assessment (ACT n=33, EME n=29). The mean age was 60±7 years and 81% were married. The mean erectile function grade pre-RP was 8.9±1 (0-10 scale). At 6m, the ACT group utilized more injections/week vs. the EM group (median: 2.06 vs. 1.17, p=0.01) and were more compliant with ICI vs. the EM group (70% vs. 45%, p=0.05, RR=1.55). The ACT group reported greater: satisfaction with ED treatment (d=0.6) and overall sexual relationship (d=0.2). The ACT group also reported lower: sexual bother (d=0.2), prostate cancer treatment regret (d=0.3), negative psychological impact of cancer (d=0.3), and depressive symptoms (d=0.2). Conclusion: Preliminary analysis suggests ACT significantly increases ICI use. Data also indicate ACT helps increase men's satisfaction with injections and sexual relationship, while reducing sexual bother, prostate cancer treatment regret, the psychological impact of cancer, and depressive symptoms. Source of funding: National Institutes of Health: R01 CA 190636 Disclosure: Work supported by industry: no.